Marine benthic cyanobacteria in the central and southern Caribbean of Costa Rica - Muñoz-Simon, Nelson (Revista Ciencias Marinas y Costeras, 2012)
Cyanobacteria constitute a group of microorganisms belonging to the Bacteria domain (Woese et al. 1990). Little has been studied about it in Costa Rica and those studies have addressed issues related to the occurrence of cyanobacteria in water treatment plants and the assessment of their potential as toxin production or pollution indicators. In the present paper the occurrence of benthic marine algae is examined in different parts of the central and southern Caribbean of Costa Rica. The results show an occurrence of 17 genera distributed among 4 Chroococcales (24%), 2 Nostocales (12%), and 11 Oscillatoriales (64%). Cyanobacteria populations remain relatively constant throughout the months of limited rainfall when the waters remain calm and clear, while in the rainy season or when there is a large amount of suspended sediments and heavy swells populations decline significantly. The genera Lyngbya, Phormidium, Oscillatoria, Spirulina and Leptolyngbya are distributed in virtually all areas sampled; however the genus Lyngbya reaches important populations in the sampling points of the central Caribbean, especially near Uvita Island where they can be found in large numbers of colonies Lyngbya majuscula and Lyngbya confervoides, species that are related to environments altered by human activity.